Prayana: Intermediated Financial Management in Resource-Constrained Settings - Mehra, Apurv; Hulikal Muralidhar, Srihari; Satija, Sambhav; Dhareshwar, Anupama; O'Neill, Jacki (CHI 2018 Conference on Human Factors in Computing Systems, 2018)
We describe the design of a novel mobile phone-based application for loan management in a resource-constrained setting. In this setting, a social enterprise manages auto-rickshaw loans for drivers, taking charge of collections. The design was informed by an ethnographic study which revealed how loan management for this financially vulnerable population is a daily struggle, and loan payment is a collaborative achievement between collectors and drivers. However, drivers and collectors have limited resources to-hand for loan management. To address this, we designed Prayana, an intermediated financial management app. Prayana shares the principles of many persuasive technologies, such as education, motivation, nudges, but is designed for users with a range of print, technical, and financial literacies and embodies the core design sensibility of enhancing users’ agency. Furthermore, it does not put the onus solely on drivers to better manage their money, instead it aims to enhance the collaborative work of loan management, supporting both the drivers and collectors.